Correlation of meiboscale symptom score and sign score for primary meibomian gland dysfunction in Indian eyes – A cross-sectional study - Prateek Nishant; Achala Ramawat; N Shrinkhal; Neeti Gupta; Sanjeev K Mittal (Indian Journal of Ophthalmology, 2022)
Purpose: To evaluate the correlation of Meiboscale with symptom score (Ocular Surface Disease Index [OSDI]) and meibomian gland dysfunction (MGD) sign score. Methods: We performed a cross-sectional hospital-based study of 53 patients of primary MGD who filled the OSDI questionnaire form and underwent complete ocular examination. The MGD sign score was calculated in both eyes using the sum of six grading systems proposed by Arita et al. in 2016. The participants underwent imaging of the upper and lower eyelids of both eyes (212 eyelids) by specular microscope. The area of meibomian gland loss (MGL) was visually assessed and scored using the Meiboscale photographic card. Correlation between these three values – OSDI score, sign score, and MGL score based on Meiboscale - was calculated using Spearman's correlation analysis and Jonckheere–Terpstra (J–T) test. Correlation coefficient rs > 0.5 was considered clinically significant. Results: Associations between MGL score and OSDI score, as well as between OSDI and sign score were statistically significant, but not clinically significant (rs = 0.3684, P < 0.001 and rs = 0.41179, P < 0.001, respectively). The association between MGL score and MGD sign score was statistically as well as clinically significant (rs = 0.8392, P < 0.001). J–T test revealed large effect size (P < 0.001, r-effect = 0.93). Conclusion: The Meiboscale card had not been tested for utility in the Indian outpatient setting yet. Meiboscale can be used for reliable assessment and grading of MGD, and has clinical utility similar to the sum of six MGD sign scores. Additionally, assessment of symptoms using OSDI or a similar questionnaire is also recommended.